CATH-2-derived antimicrobial peptide inhibits multidrug-resistant Escherichia coli infection in chickens - Hao, Shihao; Shi, Wenhui; Chen, Liujun; Kong, Tianyou; Wang, Bin; Chen, Shuming; Guo, Xiaomin (Frontiers in Cellular and Infection Microbiology, 2024)
Avian colibacillosis (AC), caused by infection with Escherichia coli (E. coli), is a major threat to poultry health, food safety and public health, and results in high mortality and significant economic losses. Currently, new drugs are urgently needed to replace antibiotics due to the continuous emergence and increasing resistance of multidrug-resistant (MDR) strains of E. coli caused by the irrational use of antibiotics in agriculture and animal husbandry. In recent years, antimicrobial peptides (AMPs), which uniquely evolved to protect the host, have emerged as a leading alternative to antibiotics in clinical settings. CATH-2, a member of the antimicrobial cathelicidin peptide family, has been reported to have antibacterial activity. To enhance the antimicrobial potency and reduce the adverse effects on animals, we designed five novel AMPs, named C2-1, C2-2, C2-3, C2-4 and C2-5, based on chicken CATH-2, the secondary structures of these AMPs were consistently α-helical and had an altered net charge and hydrophobicity compared to those of the CATH-2 (1-15) sequences. Subsequently, the antimicrobial activities of CATH-2 (1-15) and five designed peptides against MDR E. coli were evaluated in vitro. Specifically, C2-2 showed excellent antimicrobial activity against either the ATCC standard strain or veterinary clinical isolates of MDR E. coli, with concentrations ranging from 2-8 μg/mL. Furthermore, C2-2 maintained its strong antibacterial efficacy under high temperature and saline conditions, demonstrating significant stability. Similarly, C2-2 retained a high level of safety with no significant hemolytic activity on chicken mature red blood cells or cytotoxicity on chicken kidney cells over the concentration range of 0-64 μg/mL. Moreover, the administration of C2-2 improved the survival rate and reduced the bacterial load in the heart, liver and spleen during MDR E. coli infection in chickens. Additionally, pathological damage to the heart, liver and intestine was prevented when MDR E. coli infected chickens were treated with C2-2. Together, our study showed that C2-2 may be a promising novel therapeutic agent for the treatment of MDR E. coli infections and AC.